Modernism and the Frankfurt School - Miller, Tyrus (Edinburgh University Press, 2014)
Tyrus Miller's book offers readers a focused introduction to the Frankfurt School's important attempts to relate the social, political, and philosophical conditions of modernity to innovations in twentieth-century art, literature, and culture. The book pursues this interaction of modernity and modernist aesthetics in a two-sided, dialectical approach. Not only, Miller suggests, can the Frankfurt School's penetrating critical analyses of the phenomena of modernity help us develop more nuanced, historically informed and contextually sensitive analyses of modernist culture; but also, modernist culture provides a field of problems, examples, and practices that intimately affected the formation of the Frankfurt School's theoretical ideas.The individual chapters, which include detailed discussions of Walter Benjamin, Theodor Adorno, Herbert Marcuse as well as a survey of later Frankfurt School influenced thinkers, discuss the ideas of a given figure with an emphasis on particular artistic media or contexts: Benjamin with lyric poetry and architecture as urban art forms; Adorno with music; Marcuse with the liberationist art performances and happenings of the 1960s.